PERENCANAAN STRATEGIS SI/TI PADA STIKES WIDYAGAMA HUSADA MALANG DENGAN METODE WARD AND PEPPARD - Bani, Yohana Wulandari; Prasetiya, Hendro Poerbo (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2024)
The a process in identifying computer-based application mapping that is useful in helping an organization to carry out business planning and achieve targets. Stikes Widyagama Husada Malang is one of the high schools which in terms of compliance and availability of document notes on development, policies, SOPs and instructions for using Information Systems/applications cannot be properly evaluated because there is no IS/IT strategic plan. Therefore, an IS/IT strategic plan is needed In this study, the IS/IT strategy plan document was prepared at Stikes Widgama Husada using the ward and peppard research method. Ward's method is a method that consists of two stages of input and output. The input stage analyzes current conditions, and the output stage analyzes future conditions. The results of this research are in the form of an IS/IT Strategic Planning Document for Stikes Widyagama Husada for 2023-2026 in the form of a Future Application Portfolio and a road map.